2021
DOI: 10.1108/gm-04-2021-0092
|View full text |Cite
|
Sign up to set email alerts
|

Brain drain in microfinance institutions: the role of gender and organizational factors

Abstract: Purpose Uncontrollable brain drain (employees’ turnover) has been found to hamper humanitarian and sustainable objectives of socially oriented organizations. Hence, this study aims to explore the roles of gender and organizational-level factors on the rate of employees’ turnover in microfinance institutions (MFIs). Design/methodology/approach The study used an unbalanced panel data of 235 MFIs spanning the period 2010–2019. Based on the availability of the required data set on the World Bank catalogue (in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Nonetheless, differences in legal status also result in different types of agency problems that might distract the focus of microfinance objectives (Tchakoute‐Tchuigoua, 2010). For example, commercial banks often strive toward achieving financial sustainability, while NGOs try to provide services to poor people, to name a few (Nourani et al, 2022). The result of the subsample analysis (based on legal status) revealed that employee turnover has a statistically significant negative effect only for the NBFIs sample (Models 21 and 26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, differences in legal status also result in different types of agency problems that might distract the focus of microfinance objectives (Tchakoute‐Tchuigoua, 2010). For example, commercial banks often strive toward achieving financial sustainability, while NGOs try to provide services to poor people, to name a few (Nourani et al, 2022). The result of the subsample analysis (based on legal status) revealed that employee turnover has a statistically significant negative effect only for the NBFIs sample (Models 21 and 26).…”
Section: Resultsmentioning
confidence: 99%
“…For example, banks and rural banks are often subjected to prudent regulation, while NGO-MFIs can enjoy laxity in regulation. Similarly, the main objective of profit-oriented MFIs would be to maximize the profit/wealth of shareholders (Nourani et al, 2022). Hence, they would probably strive for better financial performance compared with their nonprofit counterparts.…”
Section: Modeling Employee Turnover and Financial Performance Of Mfismentioning
confidence: 99%
“…The sample consisted of only 21.4 per cent female employees, reflecting the ground reality of the gender gap in employment in MFIs. Despite the proven effectiveness of female leaders and staff in enhancing the performance of MFIs, there Contemporary Management Research 177 is low female representation in the workforce due to the challenging job nature and work environment (Nourani et al, 2021). A study of 104 Indian MFIs by Ghosh and Guha (2019) confirmed this gender gap at all levels and found that women constituted on average, 23 per cent of top management (board of directors), 8 per cent of middle management (managers/supervisors) and 11.7 per cent of lower management (staff).…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…In general, these findings suggest that higher turnover of employees results in lower OPE of MFIs due to additional costs incurred during the recruitment and training of new employees. Because the microfinance industry is an informal, labour-intensive, and relationship-based lending industry (Nourani et al, 2021), therefore, employees play a crucial role in the execution and attainment of its goals and objectives. Hence, staff attrition is certainly disadvantageous to the MFIs, as it leads to lower efficiencies.…”
Section: Institutional Factors and Performancementioning
confidence: 99%